Embracing the Complexity of Integrating Computational Thinking in Education Using Rich Pictures - Hamidi, Ali; Zerega, Rafael; Salavati, Sadaf; Milrad, Marcelo (Systems research and behavioral science, 2025)
Computational thinking (CT) is a fundamental cognitive skill that provides a problem‐solving approach applicable across various domains. Integrating CT into K–12 education is crucial for developing the competencies that students need; however, its implementation presents significant challenges. While most research on CT has focused on specific areas and stakeholders, a more systematic and holistic approach is essential for successful integration. This paper, using a systems thinking theoretical lens, explores the complexities and interdependencies of this process, informed by 5 years of empirical research. Through the development of a detailed rich picture illustrating the integration, we identified four key dimensions as leverage points within the system: context and settings, stakeholders, theoretical and pedagogical strategies, and tools and approaches. These dimensions collectively shape the educational system for CT. This paper enriches the understanding of this integration by highlighting these leverage points, setting the stage for the application of additional systems thinking tools for integrating CT into education.